ANALYSIS OF PROJECT WBS DETAILING SUFFICIENTLY QUALITY BASED ON ASSOCIATION RELATIONS - Любченко, Віра Вікторівна; Крісілов, Віктор Анатолійович (Eastern-European Journal of Enterprise Technologies, 2012)
The paper is devoted to the problem of sufficient level determination for the project WBS decomposition. It is proposed a method for WBS detailing sufficiently analyzing based on the associative relationships. It allows defining too general and too detailed WBS elements.